MARTIAL LAW AS A FACTOR IN THE PROFESSIONAL BURNOUT OF HIGHER EDUCATION TEACHERS - Melnyk , Olena; Plekan , Nataliia; Buha , Lesya; Kukharska , Liliia (Collection of scientific papers «ΛΌГOΣ», 2025)
Martial law means the need to restrict the rights and freedoms of citizens to win the war. It is also a factor that affects the workflow and psychological state of teachers. War is stress, a shift in the nervous system of any person, so it is definitely a difficult stage in the life of every teacher, since none of them has received training in working in war conditions. People do not understand the culture of safety, especially emotional and physical safety, and there is also a lack of understanding of the psychological aspect [1, p. 39].